Electrochromic compound, material and preparation method and device thereof
Through electrochemical polymerization of the conjugated donor and the non-conjugated acceptor compound monomer, a polymer with intramolecular charge migration effect is formed, which solves the problem of strong absorption of visible light by organic electrochromic materials, and achieves low driving voltage and Electrochromic materials with high color efficiency.
Patent Information
- Application Number
- CN202411322203.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-31
AI Technical Summary
Existing organic electrochromic materials have strong absorption of visible light in a neutral state, resulting in dark colors, which is not conducive to electrochromic applications.
The compound monomer using a conjugated donor and a non-conjugated acceptor is electrochemically polymerized to form a polymer with an intramolecular charge transfer effect, reducing the driving voltage and reducing the absorbance in the visible light region.
It effectively reduces the driving voltage, broadens the selection range of electrochromic materials, and improves the coloring efficiency and cycle life.
Smart Images

Figure CN119219547A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of electrochromic technology, and specifically relates to an electrochromic compound, material, preparation method and device thereof. Background Art
[0002] Electrochromic materials are a class of functional materials that have the remarkable ability to reversibly change their color or opacity when a voltage is applied. This unique property has great potential in a wide range of applications, including large displays, glare-free mirrors, and even storage devices.
[0003] Electrochromic materials include inorganic electrochromic materials and organic electrochromic materials. Organic electrochromic materials include conductive polymers, metal organic complexes, redox compounds, composite electrochromic materials, etc.
[0004] Existing organic electrochromic materials have the defect of strong absorption of visible light in the neutral state, resulting in dark color in the neutral state, which is not conducive to electrochromic applications. Summary of the invention
[0005] The following is a summary of the subject matter described in detail in this application. This overview is not intended to limit the scope of protection of this application.
[0006] The purpose of the embodiments of the present application is to provide an electrochromic compound, material, preparation method and device thereof. The specific technical scheme is as follows:
[0007] The first aspect of the present application provides an electrochromic compound, comprising: a conjugated donor and a non-conjugated acceptor, wherein the conjugated donor comprises any one or more of diphenylamine and carbazole, and the non-conjugated acceptor comprises any one or more of benzophenone or diphenyl sulfone.
[0008] In some embodiments of the present application, the molar ratio between the conjugated donor and the non-conjugated acceptor is 1:(2-2.5).
[0009] In some embodiments of the present application, the compound has the following structural formula (I) or (II):
[0010]
[0011]
[0012] Wherein, the substituent R1 is selected from any one of diphenylamine and carbazole;
[0013] The substituents R2 and R3 are each independently selected from any one of fluorine, chlorine, bromine and iodine.
[0014] In some embodiments of the present application, the compound includes any one or more of the following structural formulas:
[0015]
[0016] The second aspect of the present application is to provide an electrochromic material, which includes any one of the polymers represented by the following structural formulas P1 to P4:
[0017]
[0018]
[0019] Wherein, n refers to the degree of polymerization, which is a positive integer greater than or equal to 6;
[0020] R2 and R3 are each independently selected from any one of fluorine, chlorine, bromine and iodine.
[0021] The third aspect of the present application is to provide a method for preparing an electrochromic material, the preparation method comprising the following process:
[0022] Preparation of compound monomers: taking amino monomers, dihalogen monomers and catalysts for reaction to obtain compound monomers;
[0023] The amino monomer has the structural formula shown in X-1 below, and the dihalogen monomer has the structural formula shown in X-21 or X-22 below;
[0024]
[0025] Wherein, the substituent R4 is selected from any one of diphenylamine and carbazole;
[0026] The substituents R5 and R6 are each independently selected from any one of fluorine, chlorine, bromine and iodine;
[0027] Preparation of electrochromic material: dispersing the above compound monomer in an electrolyte, and performing electrochemical polymerization under a three-electrode system to generate any one of the polymers represented by the following structural formulas P1 to P4;
[0028]
[0029]
[0030] Wherein, n refers to the degree of polymerization, which is a positive integer greater than or equal to 6; R2 and R3 are each independently selected from any one of fluorine, chlorine, bromine and iodine.
[0031] In some embodiments of the present application, the molar ratio between the dihalogen monomer and the amino monomer is (2.2-2.5):1.
[0032] In some embodiments of the present application, the reaction temperature for preparing the compound monomer is 160° C. to 190° C., and the reaction time is 18 h to 36 h.
[0033] In some embodiments of the present application, the catalyst includes a mixture of o-phenanthroline and cuprous iodide;
[0034] The molar ratio of the o-phenanthroline to the amino monomer is (0.5-1.5):5;
[0035] The molar ratio of the cuprous iodide to the amino monomer is (0.8-1.2):10.
[0036] In some embodiments of the present application, the electrochemical polymerization method includes any one of cyclic voltammetry, constant potential method, and constant current method.
[0037] In some embodiments of the present application, the three-electrode system includes a working electrode, which includes a substrate and a conductive layer located on at least one side of the substrate;
[0038] The substrate comprises any one of glass, polybutylene terephthalate, polyurethane or polydimethylsiloxane;
[0039] The conductive layer includes any one of tin-doped indium oxide, fluorine-doped tin oxide, indium-doped zinc oxide, gallium-doped zinc oxide, antimony-doped tin oxide, and aluminum-doped zinc oxide;
[0040] In some embodiments of the present application, any one of the polymers indicated by P1 to P4 above forms an electrochromic film on at least one surface of the working electrode; the thickness of the electrochromic film is 40 nm to 160 nm.
[0041] The fourth aspect of the present application is to provide an electrochromic device, which includes the electrochromic compound described in the first aspect or the electrochromic material described in the second aspect or the electrochromic material prepared by the preparation method described in the third aspect.
[0042] The electrochromic device provided in this application can be applied to non-backlight displays, smart windows for buildings and automobiles, anti-glare rearview mirrors in cars, camouflage for individual soldiers and military equipment, intelligent thermal control of satellites, and electronic tags for commodities, etc. These devices include all the features and advantages of the electrochromic materials described above, and will not be described one by one here.
[0043] The beneficial effects of the technical solution disclosed in this application are mainly reflected in the following:
[0044] The electrochromic material provided by the present application includes a compound monomer having a non-conjugated receptor and a conjugated donor. The compound monomer forms a structure with an intramolecular charge transfer effect through a non-conjugated receptor while retaining the electrochemical polymerization site of the donor. The structure can effectively reduce the driving voltage; at the same time, since the non-conjugated receptor is introduced into the polymer side chain, the absorbance of the electrochromic material in the visible light region is effectively reduced, and the selection range of electrochemically polymerized electrochromic materials is broadened. In addition, the electrochromic material also has the advantages of high coloring efficiency and long cycle life. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] The accompanying drawings are used to provide an understanding of the technical solution of the present application and constitute a part of the specification. Together with the embodiments of the present application, they are used to explain the technical solution of the present application. The accompanying drawings are only used to illustrate the preferred implementation methods and do not constitute a limitation on the technical solution of the present application. In addition, the same reference numerals are used throughout the accompanying drawings to represent the same components.
[0046] In the attached picture:
[0047] Figure 1 is a hydrogen nuclear magnetic resonance spectrum of a monomer of a compound of some examples of the present application;
[0048] Figure 2 is an infrared spectrum of the polymer of some embodiments of the present application;
[0049] Figure 3 , Figure 4 , Figure 5 , Fig. 6A , Figure 6B and Figure 7 It is a test chart of the polymer of some examples of this application. DETAILED DESCRIPTION
[0050] In order to make the purpose, technical solutions and advantages of the present application clearer, the present application is further described below in conjunction with the accompanying drawings and specific embodiments. The embodiments in the present application can be implemented in a plurality of different forms. A person of ordinary skill in the art can easily understand the fact that the implementation and content can be transformed into various forms without departing from the purpose and scope of the present application. Therefore, the present application should not be interpreted as being limited to the contents described in the following embodiments. In the absence of conflict, the embodiments in the present application and the features in the embodiments can be combined arbitrarily with each other.
[0051] In the context of the present application, when a layer / element is referred to as being "on" another layer / element, the layer / element may be directly on the other layer / element or an intervening layer / element may exist between them. In addition, if a layer / element is "on" another layer / element in one orientation, the layer / element may be "under" the other layer / element when the orientation is reversed.
[0052] In the description of the present application, ordinal numbers such as "first" and "second" are provided to avoid confusion among constituent elements rather than to limit the quantity.
[0053] In this specification, for the sake of convenience, the words and phrases indicating the orientation or positional relationship, such as "middle", "upper", "lower", "front", "back", "vertical", "horizontal", "top", "bottom", "inside", "outside", etc., are used to illustrate the positional relationship of the constituent elements with reference to the drawings. This is only for the purpose of facilitating the description of this specification and simplifying the description, and does not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operate in a specific orientation, and therefore cannot be understood as a limitation on this application. The positional relationship of the constituent elements is appropriately changed according to the direction in which each constituent element is described. Therefore, it is not limited to the words and phrases described in the specification, and can be appropriately replaced according to the situation.
[0054] In this specification, unless otherwise clearly specified and limited, the terms "disposed" and "connected" should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection, or an electrical connection; it can be a direct connection, or an indirect connection through an intermediate, or the internal communication of two elements. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.
[0055] “A and / or B” includes the following two combinations: A only, B only, and a combination of A and B.
[0056] “At least one of A, B, and C” has the same meaning as “at least one of A, B, or C” and both include the following combinations of A, B, and C: A only, B only, C only, the combination of A and B, the combination of A and C, the combination of B and C, and the combination of A, B, and C.
[0057] Exemplary embodiments are described herein with reference to cross-sectional views and / or plan views that are idealized exemplary drawings. In the drawings, the thickness of layers and regions are exaggerated for clarity. Therefore, variations in shape relative to the drawings due to, for example, manufacturing techniques and / or tolerances are conceivable. Therefore, the exemplary embodiments should not be interpreted as being limited to the shapes of the regions shown herein, but include shape deviations due to, for example, manufacturing. For example, an etched region shown as a rectangle will typically have curved features. Therefore, the regions shown in the drawings are schematic in nature, and their shapes are not intended to illustrate the actual shape of regions of the device, and are not intended to limit the scope of the exemplary embodiments.
[0058] The following describes this in detail with reference to some specific examples.
[0059] The first aspect of the present application is to provide an electrochromic compound, which includes a conjugated donor and a non-conjugated acceptor, wherein the conjugated donor includes any one or more of diphenylamine and carbazole, and the non-conjugated acceptor includes one or more of diphenyl ketone or diphenyl sulfone.
[0060] The conjugated donor in the present application refers to a structural unit that can produce a conjugated effect (in other words, the electron orbitals of adjacent atoms or groups overlap or interact with each other) and has the ability to donate electrons.
[0061] The non-conjugated acceptor in the present application refers to a structural unit that cannot produce a conjugated effect and has the ability to accept electrons.
[0062] In the first aspect of the present application, the specific structural units of the conjugated donor and the non-conjugated acceptor are listed. These two structural units, while retaining the electrochemical polymerization sites of the donor, form a structure with intramolecular charge transfer effect through the non-conjugated acceptor, which can effectively reduce the driving voltage.
[0063] The present application discloses in some embodiments that the molar ratio between the conjugated donor and the non-conjugated acceptor is 1:(2-2.5).
[0064] The present application discloses in these embodiments that the molar ratio between the conjugated donor and the non-conjugated acceptor is any one of 1:2, 1:2.2, and 1:2.5.
[0065] The present application discloses in some embodiments that the above-mentioned compound has the structural formula of formula (I) or formula (II) shown in Table 1:
[0066] Table 1
[0067]
[0068] The substituent R1 in the above formula (I) or formula (II) is selected from any one of diphenylamine and carbazole;
[0069] The substituents R2 and R3 are each independently selected from any one of fluorine, chlorine, bromine and iodine.
[0070] The present application discloses in some embodiments that the above-mentioned compound includes any one or more of the structural formulas shown in Table 2:
[0071] Table 2
[0072]
[0073]
[0074] The second aspect of the present application is to provide an electrochromic material, wherein the electrochromic material comprises any one or more of the structural formulas shown in Table 3 below:
[0075] Table 3
[0076]
[0077] Wherein, n in Table 3 refers to the degree of polymerization, which is a positive integer greater than or equal to 6; R2 and R3 are each independently selected from any one of fluorine, chlorine, bromine and iodine.
[0078] The degree of polymerization of a polymer in this application refers to the average number of repeating units contained in the polymer macromolecular chain, represented by n, which is an indicator of the size of polymer molecules. In these embodiments, this application discloses that n is greater than or equal to 6, such as any one or more of 6 to 100,000.
[0079] The polymer of the present application includes the above-mentioned compound monomer containing both a non-conjugated acceptor and a conjugated donor. The compound monomer forms a structure with an intramolecular charge transfer effect through a non-conjugated acceptor while retaining the electrochemical polymerization site of the donor, which can effectively reduce the driving voltage; at the same time, since the non-conjugated acceptor is introduced into the polymer side chain, the absorbance of the polymer in the visible light region is effectively reduced, which broadens the selection range of electrochemically polymerized electrochromic materials. In addition, it also has the advantages of high coloring efficiency and long cycle life.
[0080] The third aspect of the present application is to provide a method for preparing an electrochromic material, the preparation method comprising the following process:
[0081] S1. preparing compound monomers: taking amino monomers, dihalogen monomers and catalysts to react to prepare compound monomers;
[0082] The amino monomer has the structural formula shown in X-1 below, and the dihalogen monomer has the structural formula shown in X-21 or X-22 below;
[0083]
[0084] Wherein, the substituent R4 is selected from any one of diphenylamine and carbazole;
[0085] The substituents R5 and R6 are each independently selected from any one of fluorine, chlorine, bromine and iodine;
[0086] The specific synthetic route is as follows:
[0087]
[0088] S2. Preparation of electrochromic material: dispersing the above compound monomers in an electrolyte salt, and performing electrochemical polymerization under a three-electrode system to generate any one of the polymers represented by structural formulas P1 to P4 in Table 3 above.
[0089] The present application discloses in some embodiments that the molar ratio between the dihalogen monomer and the amino monomer is (2.2-2.5):1.
[0090] The present application discloses in these examples that the molar ratio between the dihalogen monomer and the amino monomer is any one of 2.2, 2.3, 2.4, and 2.5.
[0091] The present application discloses in some embodiments that the reaction temperature for preparing the compound monomer is 160° C. to 190° C., and the reaction time is 18 h to 36 h.
[0092] In these embodiments, the present application discloses that the reaction temperature is any one of 160°C, 170°C, 180°C, and 190°C, and the reaction time is any one of 18h, 19h, 20h, 21h, 22h, 23h, 24h, 25h, 26h, 27h, 28h, 29h, 30h, 31h, 32h, 33h, 34h, 35h, and 36h.
[0093] The present application discloses in some embodiments that the catalyst includes a mixture of o-phenanthroline and cuprous iodide, wherein o-phenanthroline and cuprous iodide form a metal chelate for catalyzing the above reaction.
[0094] The present application discloses in some embodiments that the molar ratio between the o-phenanthroline and the amino monomer is (0.5-1.5):5.
[0095] The present application discloses in these examples that the molar ratio between o-phenanthroline and the amino monomer is any one of 0.5:5, 1:5, and 1.5:5.
[0096] The present application discloses in some embodiments that the molar ratio between the cuprous iodide and the amino monomer is (0.8-1.2):10.
[0097] The present application discloses in these examples that the molar ratio between cuprous iodide and the amino monomer is any one of 0.8:10, 0.9:10, 1:10, 1.1:10, and 1.2:10.
[0098] The present application discloses in some embodiments that in step S1, potassium carbonate is further added to the reaction system, and potassium carbonate is used to create an alkaline atmosphere to promote the reaction.
[0099] The present application discloses in some embodiments that the molar ratio of potassium carbonate to amino monomer is (2-2.2):1.
[0100] The present application discloses in these examples that the molar ratio of potassium carbonate to amino monomer is any one of 2:1, 2.1:1, and 2.2:1.
[0101] The present application discloses in some embodiments that the reaction of step S1 is carried out in an organic solvent, and the organic solvent is o-dichlorobenzene, wherein the ratio between the mass of o-dichlorobenzene and the total mass of the amino monomer and the dihalogen monomer is (3-4):1.
[0102] The present application discloses in these embodiments that the ratio between the mass of o-dichlorobenzene and the total mass of the amino monomer and the dihalogen monomer is any one of 3:1, 3.5:1 and 4:1.
[0103] The present application discloses in some embodiments that the electrochemical polymerization method includes any one of cyclic voltammetry, constant potential method, and constant current method.
[0104] The present application discloses in some embodiments that the electrochemical polymerization method is a constant potential method, and the potential is 1.1 V to 1.6 V. The present application provides the electrochemical polymerization potential in these embodiments, wherein the potential, polymerization time, etc. affect the film thickness of the electrochromic material.
[0105] The present application discloses in some embodiments that the electrolyte includes an electrolyte salt and a solvent, wherein the electrolyte salt includes any one or more of organic electrolytes such as tetrabutylammonium perchlorate, tetrabutylammonium hexafluorophosphate, lithium hexafluorophosphate, lithium perchlorate, and lithium bis(trifluoromethylsulfonyl)imide; and the solvent includes any one or more of N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), dichloromethane or acetonitrile.
[0106] The present application discloses, in some embodiments, that a three-electrode system includes a working electrode, a counter electrode, and a reference electrode.
[0107] The present application discloses in these embodiments that the counter electrode is a platinum sheet and the reference electrode is a silver / silver chloride electrode.
[0108] The present application discloses in these embodiments that the working electrode includes a substrate and a conductive layer located on at least one surface of the substrate; the substrate includes any one of glass, polybutylene terephthalate, polyurethane or polydimethylsiloxane; the conductive layer includes any one of tin-doped indium oxide (ITO), fluorine-doped tin oxide (FTO), indium-doped zinc oxide (IZO), gallium-doped zinc oxide (GZO), antimony-doped tin oxide (ATO), and aluminum-doped zinc oxide (AZO).
[0109] The present application discloses in some embodiments that any one of the polymers indicated by P1 to P4 above forms an electrochromic film on at least one surface of the working electrode; the thickness of the electrochromic film (transparent polymer film) is 40nm to 160nm.
[0110] In these embodiments, the present application discloses that the thickness of the electrochromic film is any one of 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, 160nm or any one of the values satisfying the above ranges.
[0111] The present application discloses, in some embodiments, a method for preparing an electrochromic material, the preparation method comprising the following process:
[0112] S1. Preparation of compound monomers: Add amino monomers, dihalogen monomers, potassium carbonate, o-phenanthroline, cuprous iodide and o-dichlorobenzene into a reaction device, stir and heat to react under an inert gas protection atmosphere, and after the reaction is completed, cool the reaction system, filter under reduced pressure to obtain a filtrate, distill the filtrate under reduced pressure to obtain a solid, perform chromatography on the solid, use ethyl acetate and petroleum ether (volume ratio of 1-3:1-3) as eluents, and obtain a white powder solid, which is the compound monomer.
[0113] S2, preparation of electrochromic materials: Disperse the compound monomers obtained in S1 in the electrolyte, use ITO glass as the working electrode, the working area is 1.5cm×4cm, the platinum sheet is the counter electrode, and the silver / silver chloride electrode is the reference electrode. Use constant potential polymerization method, polymerize at a voltage of 1.5V for 3min, and the compound monomers gradually polymerize on the working electrode to form a polymer. Take out the working electrode and continue to dedope in the new electrolyte under the same electrochemical conditions for 5min. Finally, take out the working electrode and rinse it with dichloromethane to obtain a transparent polymer film attached to the electrode.
[0114] The electrochromic material and preparation method thereof of the present application will be described in detail below in conjunction with specific embodiments.
[0115] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.
[0116] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.
[0117] Conventional techniques of inorganic chemistry within the art can be used in this application. In the following examples, efforts are made to ensure the accuracy of the numbers used (including amounts, temperatures, reaction times, etc.), but some experimental errors and deviations should be considered. The temperatures (in degrees Celsius) used in the following examples are expressed in ° C, and the pressure is atmospheric pressure or near atmospheric pressure. All pharmaceutical reagents are purchased at AR grade, and all reactions are carried out under argon protection. Unless otherwise noted, all reagents are obtained from commercial channels.
[0118] Example 1-1
[0119] A method for preparing an electrochromic material is provided, the method comprising the following steps:
[0120] Preparation of compound I-1: In a 50 mL three-necked flask equipped with a nitrogen vent, a thermometer, a condenser and a mechanical stirring device, 2.60 g (10 mmol) of 4-aminotriphenylamine, 4.79 g (22 mmol) of 4,4′-difluorobenzophenone, 2.76 g (20 mmol) of potassium carbonate, 0.36 g (2 mmol) of o-phenanthroline, 0.19 g (1 mmol) of cuprous iodide, and 17 mL of o-dichlorobenzene (the density of o-dichlorobenzene is 1.3 g / cm 3 ). The mixture was stirred under the protection of nitrogen atmosphere and heated to 180°C. After reacting for 32 hours, the reaction system was cooled and filtered to obtain a filtrate under reduced pressure. The filtrate was distilled under reduced pressure to obtain a solid. The obtained solid was chromatographed in a chromatography column using ethyl acetate and petroleum ether in a ratio of 1:1 (volume ratio) as eluent to obtain 4.13 g of white powder solid I-1 (yield: 63%).
[0121] Preparation of polymer P1:
[0122] 1.31 mg of monomer I-1 obtained in the above step was dissolved in 20 mL of 0.1 mol L -1 In a mixed solvent of tetrabutylammonium perchlorate in DMF and acetonitrile (volume ratio 1:4), ITO glass was used as the working electrode with a working area of 1.5 cm × 4 cm, a platinum sheet was used as the counter electrode, and a silver / silver chloride electrode was used as the reference electrode. The constant potential polymerization method was used and the polymerization was carried out at a voltage of 1.5 V for 3 minutes. The monomer I-1 gradually polymerized on the working electrode to form polymer P1. The working electrode was taken out and placed in a 0.1 mol L -1The blank solution of tetrabutylammonium perchlorate in a mixed solvent of DMF and acetonitrile (volume ratio 1:4) was subjected to the same electrochemical conditions for further dedoping for 5 minutes. Finally, the working electrode was taken out and rinsed with dichloromethane to obtain a transparent polymer film attached to the electrode with a thickness of about 90 nm.
[0123] Example 1-2
[0124] A method for preparing an electrochromic material is provided, the method comprising the following steps:
[0125] Preparation of compound I-2: In a 50mL three-necked flask equipped with a nitrogen vent, a thermometer, a condenser and a mechanical stirring device, add 2.58g (10mmol) of N-(4-amino-phenyl)carbazole, 5.02g (23mmol) of 4,4′-difluorobenzophenone, 2.76g (20mmol) of potassium carbonate, 0.36g (2mmol) of o-phenanthroline, 0.19g (1mmol) of cuprous iodide and 18ml of o-dichlorobenzene. Stir under the protection of a nitrogen atmosphere, heat to 180°C, react for 30h, cool the reaction system, filter under reduced pressure to obtain a filtrate, and distill the filtrate under reduced pressure to obtain a solid. The obtained solid is chromatographed in a chromatography column using ethyl acetate and petroleum ether 1:1 (volume ratio) as eluent to obtain 4.25g (yield 65%) of white powder solid I-2.
[0126] Preparation of polymer P2:
[0127] 1.31 mg of monomer I-2 obtained in the above step was dissolved in 20 mL of 0.1 mol L -1 Tetrabutylammonium hexafluorophosphate was dissolved in a mixed solvent of NMP and acetonitrile (volume ratio 1:4), with ITO glass as the working electrode, working area 1.5cm×4cm, platinum sheet as the counter electrode, and silver / silver chloride electrode as the reference electrode. The constant potential polymerization method was used, and the polymerization was carried out at a voltage of 1.4V for 3min. The monomer I-2 gradually polymerized on the working electrode to form polymer P2. The working electrode was taken out and placed in a 0.1mol L -1 The blank solution of tetrabutylammonium hexafluorophosphate in a mixed solvent of NMP and acetonitrile (volume ratio 1:4) was subjected to the same electrochemical conditions for further dedoping for 5 minutes. Finally, the working electrode was taken out and rinsed with dichloromethane to obtain a light yellow polymer film attached to the electrode with a thickness of about 80 nm.
[0128] Examples 1-3
[0129] A method for preparing an electrochromic material is provided, which differs from that of Example 1-1 in that:
[0130] Preparation of compound I-1: In a 50mL three-necked flask equipped with a nitrogen vent, a thermometer, a condenser and a mechanical stirring device, add 2.60g (10mmol) of 4-aminotriphenylamine, 5.44g (25mmol) of 4,4′-difluorobenzophenone, 2.76g (20mmol) of potassium carbonate, 0.54g (3mmol) of o-phenanthroline, 0.228g (1.2mmol) of cuprous iodide and 25mL of o-dichlorobenzene. Stir under the protection of a nitrogen atmosphere, heat to 180°C, react for 32h, cool the reaction system, filter under reduced pressure to obtain a filtrate, distill the filtrate under reduced pressure to obtain a solid, and chromatograph the obtained solid in a chromatography column using ethyl acetate and petroleum ether 1:1 (volume ratio) as eluent to obtain 4.4g (yield 67%) of white powder solid I-1.
[0131] Preparation of polymer P1':
[0132] The polymerization was carried out at a voltage of 1.5 V for 5 minutes to form a transparent polymer film with a thickness different from that of Example 1-1, which was about 120 nm.
[0133] Example 2-1
[0134] A method for preparing an electrochromic material is provided, the method comprising the following steps:
[0135] Preparation of compound II-1:
[0136] In a 50mL three-necked flask equipped with a nitrogen vent, a thermometer, a condenser and a mechanical stirring device, 2.60g (10mmol) of 4-aminotriphenylamine, 6.35g (25mmol) of 4,4′-difluorodiphenyl sulfone, 2.76g (20mmol) of potassium carbonate, 0.36g (2mmol) of o-phenanthroline, 0.19g (1mmol) of cuprous iodide and 25mL of o-dichlorobenzene were added. Stirring was carried out under the protection of a nitrogen atmosphere, and the mixture was heated to 180°C. After reacting for 24 hours, the reaction system was cooled, and the filtrate was filtered under reduced pressure to obtain a filtrate. The filtrate was distilled under reduced pressure to obtain a solid. The obtained solid was chromatographed in a chromatography column using ethyl acetate and petroleum ether 1:1 (volume ratio) as eluent to obtain 4.95g of white powder solid II-1 (yield 68%).
[0137] Preparation of polymer P3: Dissolve 1.45 mg of monomer II-1 obtained in the above step in 20 mL of 0.1 mol L -1In a mixed solvent of dichloromethane and acetonitrile (volume ratio 1:4) of lithium hexafluorophosphate, ITO glass was used as the working electrode with a working area of 1.5 cm × 4 cm, a platinum sheet was used as the counter electrode, and a silver / silver chloride electrode was used as the reference electrode. The constant potential polymerization method was used, and the polymerization was carried out at a voltage of 1.3 V for 2 min to 5 min. Monomer II-1 gradually polymerized on the working electrode to form polymer P3. The working electrode was taken out and placed in a 0.1 mol L -1 The blank solution of lithium hexafluorophosphate in a mixed solvent of DMF and acetonitrile (volume ratio 1:4) was subjected to the same electrochemical conditions for further dedoping for 5 minutes. Finally, the working electrode was taken out and rinsed with dichloromethane to obtain polymer films of different thicknesses attached to the electrode, with a thickness of 40nm to 160nm.
[0138] Example 2-2
[0139] A method for preparing an electrochromic material is provided, the method comprising the following steps:
[0140] Preparation of compound II-2: In a 50mL three-necked flask equipped with a nitrogen vent, a thermometer, a condenser and a mechanical stirring device, add 2.58g (10mmol) of N-(4-amino-phenyl)carbazole, 6.35g (25mmol) of 4,4′-difluorodiphenyl sulfone, 2.76g (20mmol) of potassium carbonate, 0.36g (2mmol) of o-phenanthroline, 0.19g (1mmol) of cuprous iodide and 25mL of o-dichlorobenzene. Stir under the protection of a nitrogen atmosphere, heat to 180°C, react for 24h, cool the reaction system, filter under reduced pressure to obtain a filtrate, and distill the filtrate under reduced pressure to obtain a solid. The obtained solid is chromatographed in a chromatography column using ethyl acetate and petroleum ether 1:1 (volume ratio) as eluent to obtain 4.95g (yield 68%) of white powder solid II-1.
[0141] Preparation of polymer P4: Dissolve 1.45 mg of monomer II-1 obtained in the above step in 20 mL of 0.1 mol L -1 In a mixed solvent of dichloromethane and acetonitrile (volume ratio 1:4) of lithium hexafluorophosphate, ITO glass was used as the working electrode with a working area of 1.5 cm × 4 cm, a platinum sheet was used as the counter electrode, and a silver / silver chloride electrode was used as the reference electrode. The constant potential polymerization method was used and the polymerization was carried out at a voltage of 1.3 V for 3 minutes. Monomer II-1 gradually polymerized on the working electrode to form polymer P4. The working electrode was taken out and placed in a 0.1 mol L -1 The blank solution of lithium hexafluorophosphate in a mixed solvent of DMF and acetonitrile (volume ratio 1:4) was subjected to the same electrochemical conditions for further dedoping for 5 min. Finally, the working electrode was taken out and rinsed with dichloromethane to obtain polymer films of different thicknesses attached to the electrode, with a thickness of 98 nm.
[0142] Example 2-3
[0143] A method for preparing an electrochromic material is provided. The method is different from that of Example 2-1 in that: polymer P3' is prepared by:
[0144] The polymerization was carried out at a voltage of 1.6 V for 2 minutes to form a transparent polymer film with a thickness different from that of Example 1-1, which was about 55 nm.
[0145] [Characterization]:
[0146] (1) H NMR spectrum: Bruker Avance 300 NMR spectrometer, the test solvent is deuterated chloroform (CDCl3) containing TMS.
[0147] The hydrogen nuclear magnetic resonance spectra of compound I-1 of Example 1-1 and compound I-2 of Example 1-2 were obtained, as shown in Figure 1 Schematic, where for compound I-1, the peaks are assigned to d approximately 7.88-7.85 (d), 7.55 (br), 7.49-7.37 (br), 7.33-7.25 (br).
[0148] For compound I-2, the peaks were assigned to d approximately 7.25-7.33 (br), 7.37-7.49 (br), 7.55 (br), 7.85-7.88 (d), 8.13 (s).
[0149] (2) Infrared absorption spectroscopy: Shimadzu IR Affinity-1 infrared spectrometer was used to obtain infrared spectral data of the samples by pressing the polymer powder and spectrally pure potassium bromide powder into thin sheets for testing.
[0150] The infrared absorption spectra of the polymer P1 of Example 1-1 and the polymer P2 of Example 1-2 are obtained, as shown in FIG. Figure 2 Indicate, combine Figure 2 It is known that triarylamine is 1311cm -1 (NAr3), keto group 1656cm -1 (C=O), 1153cm -1 The characteristic peaks such as sulfone group (S=O) prove the successful synthesis of the polymer.
[0151] [Performance Test]:
[0152] ① UV-visible absorption spectra of polymer P1 (Example 1-1) at different voltages:
[0153] A UV-visible spectrometer was used in conjunction with an electrochemical workstation; the electrochemical test instrument was a Shanghai Chenhua CHI660E electrochemical workstation; the UV spectrometer was a Shimadzu UV-2550 UV-vis spectrometer; in a three-electrode system test, the working electrode was an ITO glass with a polymer film, the reference electrode was a silver / silver chloride reference electrode, the counter electrode was a platinum wire electrode, and the electrolyte solution was a 0.1M tetrabutylammonium perchlorate (TBAP) solution in acetonitrile. Different constant voltages were applied to the polymer film to test the absorption changes of its UV-visible spectrum. Figure 3 , combined with Figure 3 It can be seen that the polymer film changes from light yellow to blue as the voltage increases under an external electric field.
[0154] ② Test on the change in transmittance of polymer P2 (Example 1-2) at the maximum absorption change site:
[0155] The test environment is the same as that of performance test 1, and the transmittance change of the polymer film at the maximum absorption change point is measured by square wave potentiometer.
[0156] get Figure 4 , combined with Figure 4 It can be seen that the polymer film still maintains good stability after 8000 voltage cycles.
[0157] ③ Test on the effect of polymerization time on polymer P3 (Example 2-1):
[0158] Specifically, a Bruker Dektak XT step profiler was used to test the thickness of the polymer film: a portion of the polymerized film on the ITO glass was scraped off with a knife and then the thickness was tested using the step profiler.
[0159] get Figure 5 , combined with Figure 5 It can be seen that this type of polymer can precisely control the thickness of the polymer film by controlling the polymerization time at the same voltage.
[0160] According to the above test method, the performance table of each embodiment is shown as follows:
[0161] Table 4
[0162]
[0163] ④Cyclic voltammogram of polymer:
[0164] In addition, the present application also tests and obtains the cyclic voltammograms of polymer P1 obtained in Example 1-1 and polymer P2 obtained in Example 1-2. The specific test method includes: the electrochemical test instrument is Shanghai Chenhua CHI660E electrochemical workstation; three-electrode system test, the working electrode is ITO glass with polymer film, the reference electrode is silver / silver chloride reference electrode, the counter electrode is platinum wire electrode, and the electrolyte solution is 0.1M tetrabutylammonium perchlorate (TBAP) acetonitrile solution, and the polymer film is subjected to cyclic voltammogram test. Fig. 6A and 6B .
[0165] Combined with Fig. 6A and 6B It can be seen that the starting potential of the polymer is less than 0.7 V, and the oxidation potential is less than 1.1 V. This shows that this type of polymer has a lower driving voltage in the electrochromic device, which is beneficial to improving the service life and energy saving.
[0166] ⑤ Single cycle of polymer P2 (Example 1-2):
[0167] get Figure 7 , combined with Figure 7 It can be seen that the coloring and fading time of the polymer is only 3s. The coloring efficiency of the material can be obtained by the formula η = ΔOD / Q to be 264.1cm 2 C -1 , indicating that the material prepared in the embodiment of the present application has excellent electrochromic properties.
[0168] Although the present application is in the above-mentioned FIG. 6 and Figure 7 Only some polymers are used as examples, but it is obvious that other embodiments of the present application can also achieve the same or similar technical effects.
[0169] In summary, the electrochromic material provided in this application has the advantages of low driving voltage, high coloring efficiency, and long cycle life. The devices made using this material can be applied to technical fields such as backlight-free displays, smart windows for buildings and automobiles, anti-glare rearview mirrors in cars, camouflage for individual soldiers and military equipment, intelligent thermal control of satellites, and electronic tags for commodities.
[0170] It should be understood that the terms used herein are only for the purpose of describing specific example embodiments and are not intended to be limiting. Unless the context clearly indicates otherwise, the singular forms "one", "an" and "said" as used herein may also be meant to include plural forms. The terms "include", "comprise", "contain", and "have" are inclusive and therefore indicate the presence of the stated features, steps, operations, elements and / or parts, but do not exclude the presence or addition of one or more other features, steps, operations, elements, parts, and / or combinations thereof. The method steps, processes, and operations described herein are not interpreted as requiring them to be performed in the specific order described or illustrated, unless the execution order is clearly indicated. It should also be understood that additional or alternative steps may be used. The above is only a preferred specific embodiment of the present application, but the scope of protection of the present application is not limited thereto. Any changes or replacements that can be easily thought of by a technician familiar with the technical field within the technical scope disclosed in the present application should be included in the scope of protection of the present application. Therefore, the scope of protection of the present application shall be subject to the scope of protection of the claims.
Claims
1. An electrochromic compound, characterized in that: The invention comprises a conjugated donor and a non-conjugated acceptor, wherein the conjugated donor comprises any one or more of diphenylamine and carbazole, and the non-conjugated acceptor comprises any one or more of benzophenone and diphenyl sulfone.
2. The compound according to claim 1, characterized in that: The molar ratio between the conjugated donor and the non-conjugated acceptor is 1:(2-2.5).
3. The compound according to any one of claims 1 to 2, characterized in that: The compound has a structural formula as shown in the following formula (I) or formula (II): Wherein, the substituent R1 is selected from any one of diphenylamine and carbazole; The substituents R2 and R3 are each independently selected from any one of fluorine, chlorine, bromine and iodine.
4. The compound according to any one of claims 1 to 3, characterized in that: The compound includes any one or more of the following structural formulas:
5. An electrochromic material, characterized in that: Including any one of the polymers shown in the following structural formulas P1 to P4: Wherein, n refers to the degree of polymerization, which is a positive integer greater than or equal to 6; R2 and R3 are each independently selected from any one of fluorine, chlorine, bromine and iodine.
6. A method for preparing an electrochromic material, characterized in that: The process includes the following: Preparation of compound monomers: taking amino monomers, dihalogen monomers and catalysts for reaction to obtain compound monomers; The amino monomer has the structural formula shown in X-1 below, and the dihalogen monomer has the structural formula shown in X-21 or X-22 below; Wherein, the substituent R4 is selected from any one of diphenylamine and carbazole; The substituents R5 and R6 are each independently selected from any one of fluorine, chlorine, bromine and iodine; Preparation of electrochromic material: dispersing the compound monomer in an electrolyte, and performing electrochemical polymerization under a three-electrode system to generate any one of the polymers represented by the following structural formulas P1 to P4; Wherein, n refers to the degree of polymerization, which is a positive integer greater than or equal to 6; R2 and R3 are each independently selected from any one of fluorine, chlorine, bromine and iodine.
7. The preparation method according to claim 6, characterized in that: The molar ratio between the dihalogen monomer and the amino monomer is (2.2-2.5):1; and / or; The reaction temperature for preparing the compound monomer is 160° C. to 190° C., and the reaction time is 18 h to 36 h.
8. The preparation method according to any one of claims 6 to 7, characterized in that: The catalyst comprises a mixture of o-phenanthroline and cuprous iodide; The molar ratio between the o-phenanthroline and the amino monomer is (0.5-1.5):5; The molar ratio of the cuprous iodide to the amino monomer is (0.8-1.2):
10.
9. The preparation method according to any one of claims 6 to 8, characterized in that: The electrochemical polymerization method includes any one of cyclic voltammetry, constant potential method and constant current method.
10. The preparation method according to any one of claims 6 to 9, characterized in that: The three-electrode system includes a working electrode, and the working electrode includes a substrate and a conductive layer located on at least one side of the substrate; The substrate comprises any one of glass, polybutylene terephthalate, polyurethane or polydimethylsiloxane; The conductive layer includes any one of tin-doped indium oxide, fluorine-doped tin oxide, indium-doped zinc oxide, gallium-doped zinc oxide, antimony-doped tin oxide, and aluminum-doped zinc oxide.
11. The preparation method according to claim 10, characterized in that: Any one of the polymers indicated by P1 to P4 forms an electrochromic film on at least one surface of the working electrode; the thickness of the electrochromic film is 40nm to 160nm.
12. An electrochromic device, characterized in that: The invention comprises the electrochromic compound according to any one of claims 1 to 4, the electrochromic material according to claim 5, or the electrochromic material prepared by the preparation method according to any one of claims 6 to 11.
